Sosialisasi dan Pelatihan Pemasaran Berbasis Digital Dengan Menggunakan Media Sosial pada Kelompok Tani Desa Botumoputi Kecamatan Tibawa - Saleh, Yanti; Mustafa, Ramlan; Ismail, Milawaty; Wakhidah, Nurul; Panigoro, Soraya; Ponto, Moh Fais (Jurnal Pengabdian Masyarakat Teknologi Pertanian, 2023)
ABSTRACTCorn is the most productive cereal crop in the world besides rice and wheat. Plants that can grow in high temperature areas, and cob maturation is determined by the accumulated heat obtained by the plant. Corn (Zea mays L.) is a single seed plant (monocotyledon) with rough stems ranging from 0.6 to 3 m and is a seasonal plant with an age of approximately 3 months. Botumoputi Village is one of the villages that has the largest corn producer in the Tibawa sub-district. There are 15 groups of corn farmers in the village and among them there are rice corn farmers. The results of the corn harvest are mostly sold directly without any processing into further products. Due to the lack of knowledge and knowledge they have, the harvest only flows in the market. Because marketing problems are so-so, there is a need for socialization and digital marketing training. The purpose of these activities is to provide insight and knowledge of skills and increase work creativity. Activities carried out in the hall of Botumoputi Village involved some members of the community, heads of farmer groups, PKK women and village officials. In its implementation using sustainable extension methods. The hope that can be achieved from this activity is that the people of Botumoputi Village can be more creative and can work to increase family economic income through internet networks. Keywords; marketing, corn, social media